2008
DOI: 10.1007/s12283-008-0002-3
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the muscular torques and motion-dependent torques to generate rapid elbow extension during overhand baseball pitching

Abstract: Some studies have reported that overarm baseball pitching shows a proximal to distal sequential joint motion including a rapid extension of the elbow. It has been suggested that the rapid elbow extension just before ball release is not due to the action of the elbow extensor muscles, but the underlying mechanisms are not so clear. The purpose of this study was to determine the contributions of each joint muscular-and motion-dependent torques, including the upper trunk and throwing arm joints to generate the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
0
19
1
Order By: Relevance
“…The method proposed in this study quantifies both the direct and indirect effects of individual joint torque inputs in the generation of distal-point speed, and their use for evaluating performance, whereas previous studies showed only the direct effect of joint torques in actions such as the generation of elbow extension angular velocity Naito and Maruyama, 2008), of distal-point speed (Naito et al, 2017), and of angular velocities about the longitudinal axes of the upper arm and forearm segments (Naito et al, 2014) during overarm throwing and baseball pitching, and in the generation of knee extension angular velocity during soccer kicking motion (Naito et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method proposed in this study quantifies both the direct and indirect effects of individual joint torque inputs in the generation of distal-point speed, and their use for evaluating performance, whereas previous studies showed only the direct effect of joint torques in actions such as the generation of elbow extension angular velocity Naito and Maruyama, 2008), of distal-point speed (Naito et al, 2017), and of angular velocities about the longitudinal axes of the upper arm and forearm segments (Naito et al, 2014) during overarm throwing and baseball pitching, and in the generation of knee extension angular velocity during soccer kicking motion (Naito et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies decompose the MDT into several components in order to describe how particular kinematic features of segmental and joint movements affect the MDT contributions (e.g. Hirashima et al, 2008;Naito and Maruyama, 2008;Naito et al, 2010;Naito et al, 2017;Putnam, 1991Putnam, , 1993, kinematic analyses alone cannot reveal the mechanisms by which these movements induce effective joint torques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between the slow motion serve and the normal speed serve was found to have similar trends in upper arm internal rotation (r = 0.8680, p \ 0.0001) using the Pearson's correlation test. The results from the videography, inertial gyroscopes, and MBVGs were time normalized for comparison [19,20] and are presented in the results and discussion section (see Sect. 3.2).…”
Section: Tennis Servementioning
confidence: 99%
“…In order to obtain large ball speed, the pitchers accelerate the ball by rotating their joints through exerting joint torques (e.g., [1]). Previous studies on high-seed swing motions based on multi-body dynamics have reported that motion-dependent term, which contains centrifugal force and Coriolis force, contributes largely to the generation of distal end points such as ball or hand in baseball pitching [2,3], bat head in baseball batting [4,5], racket head in tennis service [6], and so on.…”
Section: Introductionmentioning
confidence: 99%